The relationship between the arch of the foot and ankle angular range and the job done in some athletics events tendon injury Akils - Abedulnabi, Hamid (Journal of Physical Education, 2011)
The aim of research is to know the rang of angle of ankle, arch of foot and achievement occupy in some activities of track and field (Speed running – medium running – Jumping). Also aims to know the connect relation between various and degree of injury of Achilles tendon. The sample contain groups of athletes which work in research. These groups suffer from Achilles tendon. The researcher used descriptive program because it is suit to problem of research. The researcher concluded that Achilles tendon connect to rang of angle that ankle joint work and make pain when it exit in limit of big angle when the arch of foot is less, the fatigue is on connected muscles in Achilles tendon and make less that leads to reduce the injury of tendon . The researcher recommended to use mechanic points to prevent from injury of Achilles tendon